The Influence of Corporate Social Responsibility, Profitability, Liquidity, and Leverage on Tax Aggressivity - Ngurah Adi Kusuma ARTHA; Gusti Ayu Intan Saputra RINI; I Gst. Ayu Ratih Permata DEWI (Loka: Journal Of Environmental Sciences, 2023)
Purpose:The phenomenon that occurred in 2019, PT. Adaro Energy Tbk. Do something avoidance related to payment tax by implementing transfer pricing through the branch. The Company is located in Singapore and is called Coaltrade Services International. From 2009-2017, information via child company pays tax amounting to 125 million USD or Rp. 1.75 trillion ( exchange rate Rp. 14,000) or more small from it should be charged in Indonesia. Study This aims To analyze the influence of corporate social responsibility, Profitability, liquidity and Leverage on aggressiveness tax on IDX30 companies listed on the Indonesian Stock Exchange in 2020-2022.Methodology:This study is based on a deep data study, using secondary data from IDX30 companies listed on the Indonesian Stock Exchange from 2020 to 2022. 13 companies were included in the study and selected through a purposive sampling method. The data was analyzed using multiple linear regression, a statistical technique used to analyze the relationship between multiple independent variables and a dependent variable.Findings:Research results show that corporate social responsibility positively and significantly impacts aggressiveness tax. Implication:On the other hand, Profitability, liquidity, and Leverage are not influential factors in aggressive tax.